K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

12 tháng 9 2016

(x-1)4=(x-1)2

(x-1)2.(x-1)2-(x-1)2=0

(x-1)2.[(x-1)2-1]=0

(x2-2x+1).(x2-2x)=0

x4-2x3+x2-2x3+4x2-2x=0

x4-4x3+5x2-2x=0

6 tháng 1 2019

a)\(A=x^3+x^2y-xy-y^2+3y+x-1\)

               Ta có:\(x+y-2=0\Rightarrow x+y=2\)

  \(A=x^2\left(x+y\right)-y\left(x+y\right)+3y+x-1\)

     \(=2x^2-2y+3y+x-1\)

     \(=2x^2+y+x-1\)

     \(=2x^2+2-1\)

    \(=2x^2+1\)

8 tháng 1 2019

b) x - y = 0 => x = y

B = x( x^2 + y^2 ) - y ( x^2 + y^2 ) + 3

= x(x^2 + x^2 ) - x (x^2 + x^2 ) + 3

= 3

11 tháng 2 2016

2x+ 2x+1+ 2x+2 + 2x+3 = 2x+ 2x.2 + 2x.2+ 2x.23 = 2x(1+ 2 + 22 + 23) = 2x.15 = 120 => 2x =120:15 = 8 => x = 3